PKC gamma regulates connexin 57 - Snider, Adam K. (Kansas State University, 2010)
Spinocerebellar ataxia type 14 (SCA14) is a rare, autosomal dominant neurodegenerative disease caused by mutations in the gene encoding for protein kinase Cγ (PKCγ). These mutations affect the translocation and activation of the protein and are particularly damaging to the Purkinje cells of the cerebellum. This translocation and activation leads to the down regulation of gap junction activity by direct phosphorylation on the C-terminal tail of connexin proteins. This process is necessary in terminating the propagation of apoptotic signaling and is disrupted by SCA14-type mutations. Gap junctions allow the passive diffusion of small molecules from one adjoining cell to another. Gap junctions function as electrical synapses in neuronal tissue and are formed from connexin proteins. The connexin family of proteins contains approximately 20 members, each of which is expressed in a tissue dependent manner. One of the dominant connexin proteins expressed in Purkinje cells is connexin 57 (Cx57). Here, I have tested if Cx57 is regulated by PKCγ. This thesis shows that activation of PKC and PKCγ caused internalization of Cx57 gap junction plaques in HT-22 cell culture. PKC and PKCγ activation led to the phosphorylation of Cx57 primarily on serine residues. Furthermore, the expression of SCA14-type PKCγ led to increased sensitivity to oxidative stress, resulting decreased cell viability.
Keywords: Connexin 57; Spinocerebellar ataxia type 14; Protein kinase c gamma; Chemistry, Biochemistry (0487)